INOVASI TEKNIK WARMING-UP SEBAGAI JEMBATAN AKTIVASI SKEMATA DALAM PEMBELAJARAN BAHASA INGGRIS - Mutiana Nurmalasari; Desi Qoriah; Muhamad Hilman Firmansyah (Universitas Garut, 2025)
This community service activity addresses the challenge faced by prospective English instructors in Garut's tourism villages, particularly those under KNPI Garut who struggle to build active class atmospheres due to the limited use of effective warming-up techniques. The problem prevents the activation of schemata and hinders the natural transition to core material. This training aimed to enhance the instructors' understanding of warming-up as a schemata activation tool and to equip the 12 participants with three innovative techniques: Guessing Game, Describing Word Game, and Reverse Direction Game. The methodology involved intensive training, demonstration, and microteaching. The results showed a significant increase in the participants' conceptual understanding of warming-up's role. Participants successfully implemented all three techniques, with the Guessing Game proving effective in schemata activation, the Describing Word Game enhancing verbal fluency, and the Reverse Direction Game successfully boosting focus and creating a lively classroom atmosphere. The training positively impacted the instructors' pedagogical competence, allowing them to open classes in a more structured and engaging manner. Keywords: Warming-Up, Schemata Activation, English Learning, Pedagogical Competence, Tourism Village